Comparison between endoscopic and conventional dacryocystorhinostomy in the treatment of tear duct obstruction in terms of surgical success rate and recurrence rate - العلوني فايز; شقوف غرام (Latakia University Journal -Medical Sciences Series, 2022)
Purpose: comparison of surgical success rate and recurrence rate between external and endoscopic endonasal Dacryocystorhinostomy. Methods: 40 patients participated in this study (9 male, 31 female). Patients’ information was collected, including the History ,gender and age. A comprehensive eye examination was performed an Jones 1 an Jones2 eas performed to confirm the diagnosis. An otolaryngological examination was performed with a Rigid endoscopy (zero). Follow up eas for 6 monthes with three reviews to assess the success of surgical procedure by evaluating the continuity or absence of tears and knowing the complications following the surgical operation. Results: the success rate with endonasal Dacryocystorhinostomy was higher (95%) with one case of recurrence (5%) verses tow cases in external Dacryocystorhinostomy and there were no significant statistical differences ( p-value=0.5 ). Complication rate was low, with two cases of Hemorrhages with endonasal 10% verses one case in external Dacryocystorhinostomy. scaring an lip rupture have only been observed with external Dacryocystorhinostomy Dacryocystorhinostomy Also, we did not find a clinically significant change in the mean values ​​of the tear film break up time test and the Schirmer test before and after the operation. There were two patients whom experienced mild dryness using OSDI with change of eye condition to moderate dryness after surgery. Conclusion:success rate of the tow procedures is similar with low Complication rate.